Relevansi Ciri Manusia Indonesia Dalam Buku Manusia Indonesia Karya Mochtar Lubis di Era Digital - Bidayatul Hidayah; Hanum Putri Rahmadewi; Taat Wulandari (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
This study aims to analyze the relevance of the characteristics of Indonesian people as described in Mochtar Lubis’ Manusia Indonesia within the context of the digital era and Society 5.0. Indonesia, as a multicultural country, possesses diverse cultural values that shape social characteristics such as mutual cooperation, tolerance, and kinship. Along with technological advancements, these values have undergone significant transformations that require critical examination. This research employs a qualitative approach using a literature study method, with the primary data source being Manusia Indonesia and other relevant academic references. Data were collected through documentation techniques and analyzed using content analysis to identify and interpret key concepts, which were then linked to contemporary social phenomena. The results indicate that several characteristics identified by Mochtar Lubis such as hypocrisy, reluctance to take responsibility, feudal mentality, belief in superstition, artistic nature, and weak character remain relevant today. In the digital era, these traits are manifested in new forms, including the spread of misinformation, cyberbullying, imitative culture, and self-image construction on social media. However, Indonesian society also demonstrates positive potential, particularly in creativity, social solidarity, and adaptability to change. Therefore, understanding these characteristics is essential as both a critical reflection and a foundation for developing a society that is adaptive, critical, and responsible, while maintaining its national identity amid globalization.